Evaluation of post hysterectomy vaginal cuff related complications and their management after different modes of hysterectomy - Hamal, Shreejana `; Hui, Ju Wen; Rong, Wang Xian; Hui, Li (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Aim: To update the incidence of vaginal cuff related complications after different modes of hysterectomy and their management. Methods: The study was conducted in Jingzhou central hospital, Jingzhou, Hubei, China. Patient’s case files were reviewed who had undergone Hysterectomy from 1st Jan. 2013 - 31st Dec. 2014. The incidence of vaginal cuff related complications were retrospectively evaluated by different approaches. Data were collected according to our inclusion criteria and statistically analyzed its significance (P <0.05). Results: 887 patients underwent hysterectomy during 2 years of study period. Mean age was 54 ± 4 years. Overall incidence of vaginal cuff related complications were 34 (3.83%) which included vaginal cuff bleeding 12 (1.35%), vaginal cuff infections 16 (1.80%) and vaginal cuff dehiscence 6 (0.67%) without evisceration. Laparoscopic hysterectomy had higher incidence (6.12%), than open abdominal (2.56%) and vaginal (3.22%) hysterectomy. Incidences were significant (P = 0.032) to approaches of hysterectomy. The Incidence of vaginal cuff dehiscence between Laparoscopic and Open abdominal hysterectomy were significant (P = 0.015) but the incidence of vaginal cuff bleeding (P = 0.90) and vaginal cuff infection (P = 0.74) were not significant. Over all incidences were higher in malignancy (61%) than benign (20%). Conclusions: Study suggests that vaginal cuff bleeding, cuff infection, cuff dehiscence and evisceration are rare but not negligible which may lead into catastrophic conditions. Early diagnosis and appropriate management reduces further complications. Partial cuff dehiscence can be managed conservatively without surgical repair with satisfactory outcome.